Inovasi Kelembagaan Pondok Pesantren Melalui Tranformasi Nilai: Studi Kasus di Pondok Pesantren Amanatul Ummah Pacet Mojokerto - Chusnul Chotimah; Indah Khomsiyah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2019)
Islamic boarding schools are the oldest Islamic educational institutions that survive until now. The institution can survive because it continues to innovate in accordance with the demands of the times. This phenomenon also occurs in Amanatul Ummah Islamic Boarding School, which is adaptive and adoptive for the new madrasah or school system by integrating general science and religious sciences as well as preserve salafiyah values. Institutional innovation certainly does not just happen but there is a process that is taken and also the transformation of values as the power of innovation itself. The value built by Amanatul Ummah Islamic boarding school as a basic force of institutional innovation is intangible in the form of transforming the mindset of local santri-ulama towards great santri-ulama, from santri to religious professional scientist santri, from santri local businessmen to conglomerate, from traditional santri to millennial, and from closed minded to be open-minded. Whereas the process of institutional innovation was carried out as a real implementation of the intangible values ranging from unfreezing, changing and refreezing conditions, namely only Madrasah Tsanawiyah developed to Madrasah Aliyah, Excellence of Madrasah Aliyah, Accelerated of Madrasah Programs, and International of Standard Madrasah (MBI)